The Effects of Cause-Related Marketing on Customers$1 (BAttitudes and Buying Behaviors - Steckstor, Denise; SpringerLink (Online service) (Wiesbaden : Gabler Verlag, 2012)
Firms increasingly concentrate their Corporate Social Responsibility strategies within marketing by implementing Cause-Related Marketing programs. Especially against the background of an increased marketing accountability, Denise Steckstor develops a comprehensive model of Cause-Related Marketing determinants and customer attitudes as well as behavior and validates it on the basis of a quasi-experimental field study. She shows that Cause-Related Marketing programs can, additionally to generating donations for the not-for-profit partner, contribute to achieving central marketing goals. Based on her findings, she provides an overview for marketing managers on how to effectively design and manage Cause-Related Marketing programs.
Keywords: Economics; Marketing; Economics/Management Science; Marketing